Methodology for easing the deployment of cattle raising georeferencing tracing technologies on Colombian Farms. Case Study (2021)
The livestock sector is fitted with modern technology that has been developed and implemented in several countries. However, according to FEDEGAN, in Colombia, more than 65% of farms have a low technological level and the modernization of the sector is subject to considerable improvements applying georeferencing technologies. Therefore, this research project develops a methodology for the application of georeferencing technologies in the livestock sector of Colombia. The proposed methodology is based on concepts of Agile methodologies and develops 4 sequential stages that guide the Colombian farmer in the integration of these technologies to its farm. The initial stage identifies and characterizes the farmer’s requirements, applying an adaptation of the Quality Function Deployment (QFD). According to the results, it is proposed the use of the Analytical Hierarchical Process (AHP) to select the device that matches the farmer’s criteria. The second stage includes purchasing the proper device based on the previous stage's insights. The third stage guides the farmer in the testing of the device selected, and finally, in the fourth stage, a proposal of how to analyze the data obtained by the georeferencing device is presented. The results of the methodology were validated by an expert panel through a focus group, and by a case study. de grado.